2008
DOI: 10.1289/ehp.10490
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Thyroid Hormone Levels to Levels of Polychlorinated Biphenyls, Lead, p,p- DDE, and Other Toxicants in Akwesasne Mohawk Youth

Abstract: BackgroundIt is well documented that acute exposure to high levels of persistent organic pollutants, such as polychlorinated biphenyls (PCBs), p,p′-dichlorophenyldichloroethylene (p,p′-DDE), and hexachlorobenzene (HCB), can affect human health including thyroid function. Chronic exposure to multiple toxicants is common but difficult to analyze, and most prior studies have focused on adults or newborns, creating a gap in our understanding of multitoxicant effects among adolescents.ObjectiveWe investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 107 publications
(126 reference statements)
2
53
2
2
Order By: Relevance
“…Furthermore, the OH− PBDEs may act together with other TTR-binding environmental chemicals and hamper TH homeostasis at different physiological levels and via multiple related mechanisms. 35 Admittedly, these estimations are based on our in vitro experimental data and therefore cannot be directly extrapolated to in vivo conditions. …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, the OH− PBDEs may act together with other TTR-binding environmental chemicals and hamper TH homeostasis at different physiological levels and via multiple related mechanisms. 35 Admittedly, these estimations are based on our in vitro experimental data and therefore cannot be directly extrapolated to in vivo conditions. …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Table II summarizes various cohort studies in which PCB exposure was correlated to a disruption of 7 circulating levels of THs in humans. In several studies, environmental PCB levels were shown to be associated with reduced TH levels [17][18]20].…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%
“…There is evidence that exposure to DDT in utero may also affect thyroid hormone levels (AlvarezPedrerol et al, 2008;Nagayama et al, 2007;Schell et al, 2008). Inconsistent evidence is emerging that high blood concentration of DDTs may affect height, body mass index and other measures of growth in children (Eskenazi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%